Sentiment Analysis With Transformers Applied to Education: Systematic Review. - Pilicita Garrido, Anabel; Barra, Enrique (International Journal of Interactive Multimedia and Artificial Intelligence, 2025)
Sentiment analysis, empowered by artificial intelligence, can play a critical role in assessing the impact of cultural factors on the advancement of Open Science and artificial intelligence. Additionally, it can offer valuable insights into the open data gathered within educational contexts. This article presents a systematic review of the use of Transformers models in sentiment analysis in education. A systematic review approach was used to analyze 41 articles from recognized digital databases. The results of the review provide a comprehensive understanding of previous research related to the use of Transformers models in education for the task of sentiment analysis, their benefits, challenges, as well as future areas of research that can lay the foundation for a more sustainable and effective education system.